ETHICAL AND LEGAL ASPECTS OF INFECTOLOGY AND VACCINE PROPHYLAXIS. Part 1. Bioethics and social justice in infectious pathology - O. I. Kubar (Инфекция и иммунитет, 2014)
Abstract. The serial materials on the history of establishment and the modern concepts of bioethics in the field of infectious pathology is planned to present in several articles. In the current report problems of forming and compliance of social responsibility are considered. It is demonstrated the universal importance of ethic principles and specificity of their realization in the different stages of combating with infectious diseases.